PSYCHOSOCIAL ASPECTS OF AGING IN WOMEN - Castaño, Dolores; Martínez-Benlloch, Isabel (Anales de Psicología / Annals of Psychology)
This paper analyses the special aspects of aging in women, such as the role of women in our society and its effect on aging. The consequences of menopause and housekeeping on retirement are also reviewed.